Implementation of online problem-based learning assisted by digital book with 3D animations to improve student's physics problem-solving skills in magnetic field subject - Binar Kurnia Prahani; Iqbal Ainur Rizki; Khoirun Nisa'; Nina Fajriyah Citra; Hanan Zaki Alhusni; Firmanul Catur Wibowo (OmniaScience, 2022)
The magnetic field is a more complex and abstract physics subject than other physics subjects, causing students' low ability to solve problems. So there is a need for learning instruments to overcome these problems, especially when online learning during the COVID-19 pandemic. Research creates and implements an online problem-based learning (OPBL) assisted by digital books with 3D animation to improve students' physics problem-solving skills on magnetic field subjects. Research aimed to analyze the validity, effectiveness, and student responses to the learning instruments used. The method used in this research is quantitative by using quasi-experiment and survey methods. The results showed that this learning instrument was valid and reliable to use in terms of content and constructs. According to statistical test results, this learning instrument is also effective in improving students' problem-solving skills on magnetic field subjects. Furthermore, the student's response to this learning instrument was very positive, making this learning activity more innovative and fun. Research implies that an OPBL assisted by digital books with 3D animation instruments can be a solution to improve students' physics problem-solving skills, especially during the online learning period.